2009
DOI: 10.1093/eurjhf/hfp021
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose nitroglycerin improves microcirculation in hospitalized patients with acute heart failure

Abstract: AimsImpaired tissue perfusion is often observed in patients with acute heart failure. We tested whether low-dose nitroglycerin (NTG) improves microcirculatory perfusion in patients admitted for acute heart failure. Methods and resultsIn 20 acute heart failure patients, NTG was given as intravenous infusion at a fixed dose of 33 mg/min. Using Sidestream Dark Field (SDF) imaging, sublingual microvascular perfusion was evaluated before (T0, average of two baseline measurements) and 15 min after initiation of NTG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…The method is based on the oxygen dependent decay of delayed fluorescence of endogenously present mitochondrial protoporphyrin IX (P p IX) [24]. Proof of concept measurements were initially performed by Mik et al in single cells and later validated in vivo in rat liver and recently also in the heart [24,25]. Deconvolution of the decay curves allowed mit pO 2 histograms to be generated and showed a heterogeneous distribution of mit pO 2 values.…”
Section: Recent Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method is based on the oxygen dependent decay of delayed fluorescence of endogenously present mitochondrial protoporphyrin IX (P p IX) [24]. Proof of concept measurements were initially performed by Mik et al in single cells and later validated in vivo in rat liver and recently also in the heart [24,25]. Deconvolution of the decay curves allowed mit pO 2 histograms to be generated and showed a heterogeneous distribution of mit pO 2 values.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…One of the remarkable measurements of the mit pO 2 values was the finding of mit pO 2 values much higher (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) than previously thought (less than 5 mmHg) and secondly the finding of markedly heterogeneous mit pO 2 values, similar to the distributions of microvascular pO 2 measurements using P p IX quenching of phosphorescence we had measured in heart [24]. Indeed (early) observations of the heterogeneous state of myocardial and mitochondrial energy states underscores the importance of heterogeneity of oxygen delivery and utilization [3].…”
Section: Recent Developmentsmentioning
confidence: 99%
“…Furthermore, vasodilators could also act on microcirculation reducing shunt areas and improving organ perfusion. Recently, den Uil et al demonstrated that nitroglycerin, a known vasodilator with NO donor properties, was able to reverse microcirculatory abnormalities in patients with acute heart failure (37) . However, whether correcting microcirculatory dysfunction will be associated with the improvement of patient outcome in a microcirculation-guided approach still remains to be proved.…”
Section: Heart Failurementioning
confidence: 99%
“…However, no effect could be seen in endothelial histological injury or tissue factor expression in this same model. Nitroglycerin effects on microcirculation derangements had been tested in heart failure (37) and sepsis (60) . In acute heart failure, low doses of nitroglycerin (33 µg/min) increased perfused capillary density (assessed by SDF) for about 15% (37) .…”
Section: Vasodilatorsmentioning
confidence: 99%
See 1 more Smart Citation